Bullying at Workplace affecting Motivation and Organizational Citizenship Behavior of Branch Banking Staff in Major Cities of Pakistan - Syed Fahad Ali; Mubeen Butt (Entrepreneurship Faculty, Universitas Garut, 2021)
Banking Sector has been considered as one of the top career priority choices of University Graduates in Pakistan over the past decades. But since the Bank’s got privatized branch banking has mainly observed as one of the most hatred areas of deployment for any employee. The objective of this investigation was to analyze that Bullying affects motivation and employees consider it as part of the routine and stays motivated and committed to their organization, which is possible because of several reasons in which one could be fewer job opportunities and financial issues. Results of this investigation will help the Banks management for decision making in order to improve their working culture and will also trigger future researchers to further investigate these findings. We took Branch Banking Staff from all banks across Pakistan as a population and could manage a sample size of 271 (validated as 248) from different cities and brands of Banks under the snowball sampling technique by using cross sectional research design. Data was collected through structured questionnaires via google forms with help of social media forums. Data Analysis was conducted through SPSS and in initial analysis, we didn’t find any symptoms of multicollinearity in our data therefore the linear relationship between Motivation (IV) and OCB (DV) was found. Further Pearson correlation reflected a significant and positive relationship between motivation and ocb. 71% variation was explained through the regression model of motivation and ocb with positive relationship, whereas Moderation of Bullying was proved with 35% variation explained.